DIFFICULTIES IN CONVEYING RUSSIAN HUMOR WHEN TRANSLATING INTO ENGLISH (Journal of Universal Science Research, 2025)
The issues of humor translation in works of fiction are always relevant due to cultural and historical features. This paper examines the difficulties that arise when translating a comic based on the work "Monday Begins on Saturday" by A. N. and B. N. Strugatsky, which is the novelty of the study. The purpose of the work is to examine the comic moments of the original text and their translation in order to identify the transformations applied and determine whether the comic effect has been preserved.